Development of Interactive Multimedia Using Problem Based Learning Model in Class VIII Integrated Science Subjects Junior High School - Hakim, Lukman; Bentri, Alwen; Hidayati, Abna; Amilia, Winanda (UNDIKMA, 2023)
This study addresses low student learning outcomes due to limited use of interactive multimedia and lack of interest in learning using the same model. The aim is to develop valid and practical interactive multimedia through a problem-based learning approach for science subjects. This research is a development research (R&D) with the ADDIE development model. The results of research on learning media development by media validator 1 were obtained